Effects of perceived authenticity on value, customer satisfaction and behavioural intention towards Nyonya restaurants in Melaka, Malaysia - Ng, Chien Ying (2017)
Nyonya cuisine has been garnering more national attention due to its unique taste. The popularity of the cuisine spurred the growth of Nyonya restaurants in Melaka, a state declared as a UNESCO World Heritage. This study intended to identify how perceived authenticity of food, atmospherics, and service employees influenced customer perceived value, customer satisfaction, and future behavioural intentions towards Nyonya restaurants. The mediating roles of perceived value and customer satisfaction were also examined. Lastly, the moderating effect of familiarity with Nyonya restaurants on the relationships between perceived authenticity dimensions, perceived value, customer satisfaction, and behavioural intentions were investigated. A convenience sampling was carried out at two Nyonya restaurants in Melaka whereby self-administered questionnaires were distributed to the customers. A total of 336 usable responses were used for data analysis. The proposed structural model of this study was tested following Anderson and Gerbing’s (1988) two-step approach: a measurement model and a subsequent structural model. Using the structural equation modeling (SEM) technique, this study discovered that positive perception of food authenticity was statistically significant in inducing higher perceived value, greater customer satisfaction, and positive behavioural intentions. Service employee authenticity was a significant antecedent of perceived value. Perceived value was found to affect behavioural intentions through customer satisfaction. In addition, perceived value acted as a partial mediator in the relationship between food authenticity and customer satisfaction and a full mediator in the relationship between service employee authenticity and customer satisfaction. Customer satisfaction also served as a partial mediator between food authenticity and behavioural intentions.The results of chi-square difference test indicated that the relationships among perceived authenticity dimensions, perceived value, customer satisfaction, and behavioural intentions were significantly different according to customer familiarity levels with Nyonya restaurants. In particular, the statistical tests disclosed that the moderating function of familiarity existed in the relationships between: (i) atmospherics authenticity and perceived value; (ii) food authenticity and customer satisfaction; (iii) atmospherics authenticity and customer satisfaction; (iv) atmospherics authenticity and behavioural intentions; (v) service employee authenticity and behavioural intentions; and (vi) perceived value and behavioural intentions. The findings provided important implications for selecting and refining the critical authenticity aspects of Nyonya restaurants in order to increase perceived value, enhance customer satisfaction, and eventually intensify positive behavioural consequences. Unlike previous studies on restaurant authenticity, this study exclusively investigated the effects of perceived authenticity from the aspects of food, atmospherics, and service employees on customers’ post-dining behaviours in Nyonya restaurants. This study could also offer directions to improve customers’ perceived authenticity which can thus enrich their dining experience.